Device profile of exAblate Neuro 4000, the leading system for brain magnetic resonance guided focused ultrasound technology: an overview of its safety and efficacy in the treatment of medically refractory essential tremor. (4th May 2021) - Jameel, Ayesha; Bain, Peter; Nandi, Dipankar; Jones, Brynmor; Gedroyc, Wladyslaw
ABSTRACT: Introduction: Magnetic Resonance guided Focused UltraSound (MRgFUS) is an emerging technique that utilizes multiple high-energy low-frequency ultrasound beams generated from a multi-element transducer focused onto a single site to cause thermal ablation of the target tissue. The ExAblate Neuro 4000 system is the leading MRgFUS brain system, performing targeted thermal ablation on specific nuclei in the brain. Its precision targeting opens up new and exciting possibilities for future treatments of a wide range of neurological diseases.  Areas covered: This article aims to introduce the non-expert reader (clinician and non-clinicians) to the role of the ExAblate Neuro 4000 System in brain MRgFUS. The current clinical uses of the ExAblate system in the brain are explored with a particular focus on Essential Tremor, where internationally there is most experience, this includes reference to current literature. The safety and efficacy of MRgFUS treatments are explored and the challenges the ExAblate system must overcome to balance these juxtaposed outcomes.Expert opinion: We describe the hopes for future clinical uses of the ExAblate Neuro 4000 system to treat neurological disease and consider further advancements in MRgFUS transducer technology that may open up new exciting frontiers within the brain.